A Review and Comparative Study of On- and Off-Body Performance of Platform-Tolerant UHF RFID Tag Antennas - Gardill, Markus; Finkenzeller, Klaus; Hinz, Walter; Fischer, Georg; Weigel, Robert; Kölpin, Alexander (8th International Conference on Body Area Networks, 2013)
This paper addresses the remote identifying of human subjects by means of UHF RFID tags. In particular, we provide a comprehensive review of recent approaches in the design of compact, platform-tolerant UHF RFID antennas for on- as well as off-body applications. We first categorize previously published antenna designs and interrelate the various approaches. We then provide detailed simulation results for several selected design approaches, and compare the performance of the proposed antenna structures when used in free-space, placed in proximity to a homogenous phantom half-space model, and when used on or in proximity to a layered elliptical body model. We provide a comparative study by evaluating all approaches using the same figure of merits, which are the power transfer and the estimated read range, evaluated in exactly the same simualtion environment for all approaches.
elib2cris::1512001600,gardill2013f